Supplementary winter feeding is associated with higher recruitment rates in a population of a scavenging bird of prey - Nebel, Carina; Penttinen, Ida; Laaksonen, Toni (Springer Nature, 2026)
Supplementary feeding is a widely used conservation strategy to support scavenging species, but the full effects remain poorly understood. In the Baltic Sea region, the recovery of the white-tailed eagle (Haliaeetus albicilla) was assisted by an extensive feeding scheme. We examined whether the individual usage of a feeder was associated with the probability to recruit into the local population. At a feeder in Southwest Finland, food was offered during winter, and visiting individuals were identified based on their unique ring codes. In addition, we identified individuals by genotypes extracted from feathers collected from ringed nestlings and from adult feathers collected from nests between 2003 and 2012 and 2008 and 2023, respectively. By matching nestling and adult genotypes, we infer recruitment and relate it to feeder usage. In addition, we explore sex-specific differences, which could arise due to intra-specific competition due to size differences. Our findings reveal that there was high individual variability in feeder usage and that visitation rate was positively associated with the probability to recruit. Although females spent more time at the feeder, recruitment was irrespective of sex. While for individuals the probability to recruit increased from 13.6% to 43.0%, the population-level increases were small, from 13.6% to 14.7%. We demonstrate that winter feeding had the potential to aid the recovery of the white-tailed eagle in the region, although estimating the full effect of supplementary food for the population would require further analyses. Our study highlights the consequences of supplementary feeding and facilitates more informed management strategies for the conservation of endangered species.